Characterization of patients with home care indication in the city of Vitória – ES (Research, Society and Development, 2022)
The modality of home care is expanding in Brazil and in the world, favoring the treatment of elderly patients and those with chronic diseases, who often have limited mobility. In 2011, the Federal Government launched the Better at Home Program, for structuring home care. Objective: this research aims to outline the profile of bedridden users who need home care in a municipality in the southeastern region of Brazil. Methodology: this is an exploratory and descriptive research with a quantitative approach. The research was developed in the city of Vitória - ES. The identification of the epidemiological profile of bedridden patients with indication of receiving home care was carried out, through electronic medical records. The data collected were from the years 2019 and 2020. Results: during the study period, we found 298 bedridden patients who needed home care. Most of these patients are female, elderly over 75 years of age, white, married or in a stable relationship, with medium family risk and high clinical-functional vulnerability index. Conclusion: based on the results found, it is possible to develop protocols and flowcharts to implement the Better at Home Program in that municipality. Characterizing the profile of bedridden patients who would be treated in the program allows the direction of the teams aiming at quality care.